Impact of C-reactive protein–albumin–lymphocyte (CALLY) index on prognosis after hepatectomy for colorectal liver metastasis. (April 2023) - Furukawa, Kenei; Tsunematsu, Masashi; Tanji, Yoshiaki; Ishizaki, Shunta; Akaoka, Munetoshi; Haruki, Koichiro; Uwagawa, Tadashi; Onda, Shinji; Matsumoto, Michinori; Ikegami, Toru
Abstract: Aim: The C-reactive protein (CRP)-albumin-lymphocyte (CALLY) index is a novel inflammation-based biomarker. We aimed to investigate whether the CALLY can predict the prognosis in patients with colorectal liver metastases (CRLM) after hepatic resection. Methods: We included 183 patients with CRLM who underwent hepatectomy. The CALLY index was defined as (albumin × lymphocytes)/(CRP × 10 4 ). We investigated the association of the CALLY index with overall survival by univariate and multivariate analyses. Results: In total, 101 (55%) patients had a low CALLY index (<4). In the univariate analysis, overall survival was significantly worse in patients with lymph node metastases ( p = 0.02), extrahepatic lesions ( p < 0.01), and a low CALLY index ( p < 0.01). In the multivariate analysis, independent and significant predictors of overall survival were lymph node metastases ( p = 0.04), extrahepatic lesions ( p = 0.03), and a low CALLY index ( p = 0.03). Patients with a low CALLY index had significantly more postoperative complications than those with a high CALLY index (29% vs. 11%, p < 0.01). Conclusion: The CALLY index may be an independent and significant indicator of outcomes in patients who underwent liver resection for CRLM. Highlights: The C-reactive protein-albumin-lymphocyte (CALLY) index is a novel inflammation-based biomarker. The prognostic value of the CALLY index in patients with colorectal live rmetastases (CRLM) who underwent hepatectomy has not been reported. The CALLY index was an independent and significant indicator of outcomes in patients who underwent hepatectomy for CRLM. Also, patients with a low CALLY index had significantly more postoperative complications than those with a high CALLY index.